About the image of mother with child in fine arts. Part II. Renaissance - N. A. Makatsariya (Акушерство, гинекология и репродукция)
The article highlights aspects of the topic a mother and a child in fine arts of the Renaissance. Paintings by Dutch artists Robert Campen and Jan Van Eyck, Italian paintings by Leonardo da Vinci, Michelangelo, Sandro Botticelli, Raphael, as well as paintings by Diego de Silva y Velazquez, Peter Paul Rubens and Rembrandt are presented.